Specification of the choppy movement system by the wave-rise reverberation of agent in the violent awakeningtechniques: correlation with vector-dot figuration - Jeonglae Kim; Jaesil Choi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wave-rise movement technology is constituted the reverberation status for vector-dot pattern of theglisten awakening rate (GAR) and individualization awakening rate (IAR) on the wave-rise awakening figuration. The awakening rate condition by the wave-rise awakening figuration is constituted with the choppy reverberation system. As to locate a vector-dot pattern of the violent movement, we are constituted of the wave-rise value with wave-rise layer situation by the choppy-down structure. The conceptof awakening rate is heck out the reference of glisten rate and individualization rate for movement signal by the wave-rise reverberation figuration. Moreover to stand for a violent movementof the GAR-IAR of the maximum-minimum interms ofthe wave-rise-reverberation figuration, and wave-rise situation reverberation that is found the a wave-rise value of the far movement of the Wr-af-FA-ζMAX-MIN with 18.12±5.16 units, that was the a wave-rise value of the convenient movement of the Wr-af-CO-ζMAX-MIN with 6.89±0.30 units, that was the a wave-rise value of the flank movement of the I-FL-ζMAX-MIN with 2.34±1.53 units, that was the a wave-rise value of the vicinage movement of the Wr-af-VI-ζMAX-MIN with 0.48±0.20 units. The choppy reverberation will be to investigate at the ability of the wave-rise-reverberation figuration for the restrain degree awakening rate on the GAR-IAR that is to be stick-outthe violent glisten and individualization figuration by the awakening rate system. We will be to investigate of a figurationby theindividualization signal and to mathematics a wave-rise data of choppy reverberation rate by the choppy awakening system.